PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI)DENGAN MENGGUNAKAN MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN AKTIVITAS BELAJARDAN HASIL BELAJAR SISWA DI SMA N09 KOTA BENGKULU - Isna Mutaqwiyati; Nurhamidah Nurhamidah; Hermansyah Amir (ALOTROP, 2018)
This research was aimed to find out the student’s improvement of  learning activity and learning outcome as the implementation of  Problem Based Instruction (PBI) by using audio-visual media. The subject of this research was the students at grade X MIPA 3 of SMA N 09 Bengkulu Ciyty academic year of 2017/2018 which consisted of 27 students, on the subject of of chemistry’s basic laws and stoichiometry. This research was conducted by the researcher by using three cycles which consisted of four steps; planning, action, observation and reflection. The data collections were tests and non tests which consisted of post test and student’s learning activity observation sheets. The data of this research was analyzed by using simple quantitative data analysis;   the student’s average score, the percentage of classical absorption and the percentage of classical learning mastery.   Based on the result of this research can be concluded that the implementation of   PBI by using audio-visual media improved student’s learning activity and learning outcomes in each cycle and achieved the clasical learning outcomes in cycle III. The improvements of student’s average score was; score 23 (Fair) of cycle I; score 26,33 (good) of cycle II; and score 28,66 (good) cycle III. The average score of teacher observation sheets of each cycles were; 25,66 fpr the first cycle (good), 28 for the second cycle (good), and 29,66 in the last cycle (good). There  was also  improvements of the students’ percentage of classical learning mastery from in cycle I 51,85%, to 66,66% in cycle II and 85,15% in cycle III.